2011
DOI: 10.1002/pon.2062
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Functional Assessment of Chronic Illness Therapy—Spiritual Well‐being (FACIT‐Sp) in an Arabic‐speaking, predominantly Muslim population

Abstract: This first study of Arabic-speaking, predominantly Muslim Jordanian cancer patients using the FACIT-Sp indicates that it is a psychometrically sound instrument for detailed assessment of the spiritual well-being of Arabic-speaking cancer patients. The three-factor model appears to allow for discrimination among factors that are most highly associated with different aspects of HrQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
74
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 41 publications
12
74
1
1
Order By: Relevance
“…A positive association between overall SpWB and QOL remained significant after controlling for demographic and clinical variables 14,[20][21][22]32,34,36,43 with the exception of one study 44 (see Table 3). However, this positive association (ranges from 0.36 to 0.70) was not equal when QOL was broken down into its physical (ranges from 0.22 to 0.54), social (ranges from 0.24 to 0.54), emotional (ranges from 0.27 to 0.58), and functional dimensions (ranges from 0.38 to 0.67).…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 95%
See 4 more Smart Citations
“…A positive association between overall SpWB and QOL remained significant after controlling for demographic and clinical variables 14,[20][21][22]32,34,36,43 with the exception of one study 44 (see Table 3). However, this positive association (ranges from 0.36 to 0.70) was not equal when QOL was broken down into its physical (ranges from 0.22 to 0.54), social (ranges from 0.24 to 0.54), emotional (ranges from 0.27 to 0.58), and functional dimensions (ranges from 0.38 to 0.67).…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 95%
“…Except for two studies, 11,24 overall SpWB revealed the lowest magnitude of association with the physical dimension of QOL, whereas the association with the emotional or functional dimensions was stronger. Lazenby and colleagues, in their investigations in Jordan with predominantly Muslim patients, identified an inverse association between overall SpWB and both the emotional 22,23 and physical dimensions of QOL. 23 These findings were not replicated in a recent study with 153 subjects diagnosed with cancer in an Iranian Muslim population.…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations